1983
DOI: 10.1017/s0001566000005109
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis in Monozygotic Twins: A Case Report

Abstract: A case report is given of a pair of monozygotic twin girls with neurofibromatosis caused by a new mutation. The symptomatology was dominated by a neurofibrosarcoma on the leg of one twin and by a large plexiform neurofibroma on the neck of the other twin. Otherwise, the disease showed similar, although not identical or mirror-image distribution of subcutaneous neurofibromas and café-au-lait spots. The twins had identical HLA and blood group antigens and the same chromosome aberration. These case reports indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
3
8
0
Order By: Relevance
“…Whole body MRI of the remaining twins could be helpful in determining if paraspinal tumors exist in other twin pairs and if they are concordant. Malignancy, particularly MPNST, was discordant in one of our teenaged twin pairs (the pair with extensive paraspinal tumors) as well as one pair reported in the literature [Akesson et al, 1983], again supporting a random second hit event hypothesis. However, the sample size is small and it is therefore difficult to draw conclusions.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Whole body MRI of the remaining twins could be helpful in determining if paraspinal tumors exist in other twin pairs and if they are concordant. Malignancy, particularly MPNST, was discordant in one of our teenaged twin pairs (the pair with extensive paraspinal tumors) as well as one pair reported in the literature [Akesson et al, 1983], again supporting a random second hit event hypothesis. However, the sample size is small and it is therefore difficult to draw conclusions.…”
Section: Discussionsupporting
confidence: 80%
“…The skewed sex ratio with 90% female in our report is likely due to the small sample size since this ratio has not been previously described in twins with NF1. In reviewing the published cases where gender was reported, 6 of 13 pairs (46%) of MZ NF1 twins were of male gender, not different from the population ratio [Vaughn et al, 1981;Cartwright, 1982;Akesson et al, 1983;Crawford and Buckler, 1983;Pascual-Castroviejo et al, 1988;Craigen and Clarke, 1995;Kelly et al, 1998;Koul et al, 2000;Tubridy et al, 2001;Payne et al, 2003;Lubinsky, 2006;Kaplan et al, 2010]. Fifty percent of twin pairs in our study were de novo mutations, as expected with the known new mutation rate of the NF1 gene.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Twin studies have historically been a valuable tool for studying genetic disorders. The literature reports at least 30 pairs of proven MZ twins with NF1 [Brady, ; Vaughn et al, ; Cartwright, ; Akesson et al, ; Crawford and Buckler, ; Bauer et al, ; Pascual‐Castroviejo et al, ; Craigen and Clarke, ; Kelly et al, ; Tubridy et al, ; Koul et al, ; Payne et al, ; Lubinski, ; Sabbagh et al, ; Rieley et al, ]. In a population of 175 individuals from 48 families with NF1, Easton et al [1993] found that phenotypic features varied to a greater degree with increasing distance from a proband, with six pairs of MZ twins having the closest agreement in traits such as presence of neurofibromas, head circumference and learning disabilities, compared to more distant relatives with NF1.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, this concordance is readily explicable, not simply in terms of the presence of identical mutations in the MZ, but also as a consequence of the virtual genetic identity of the MZ genome-wide, and their shared experience of very similar pre-and peri-natal environments. Cases of MZ with NF1 who differ quite markedly with respect to the clinical manifestations of the disease have however also been reported [Akesson et al, 1983;Bauer et al, 1988;Kelly et al, 1998;Koul et al, 2000;Detjen et al, 2007] testifying to the likely complexity of the underlying biology. However, the causative mutation has not been identified in such cases and the nature of the factors responsible for bringing about the discordance of clinical symptoms in these MZ twin pairs has remained enigmatic.…”
Section: Introductionmentioning
confidence: 99%